Safety and clinical activity of atezolizumab in head and neck cancer: results from a phase I trial. (13th September 2018) - Colevas, A D; Bahleda, R; Braiteh, F; Balmanoukian, A; Brana, I; Chau, N G; Sarkar, I; Molinero, L; Grossman, W; Kabbinavar, F; Fassò, M; O'Hear, C; et al.
Abstract: Background: Head and neck cancer (HNC) has a poor prognosis at advanced stages. Given the immunosuppressive tumor microenvironment in HNC, inhibition of the programmed death-ligand 1/programmed death-1 (PD-L1/PD-1) signaling pathway represents a promising therapeutic approach. Atezolizumab (anti-PD-L1) is efficacious against many tumor types. Here we report the clinical safety and activity from the HNC cohort of the phase Ia PCD4989g clinical trial. Patients and methods: Patients with previously treated, advanced HNC received atezolizumab i.v. every 3 weeks for 16 cycles, up to 1 year or until loss of clinical benefit. Patients were monitored for safety and tolerability and evaluated for response at least every 6 weeks. Baseline PD-L1 expression level and human papillomavirus (HPV) status were evaluated. Results: Thirty-two patients were enrolled; 7 patients (22%) had a primary tumor in the oral cavity, 18 (56%) in the oropharynx, 1 (3%) in the hypopharynx, 2 (6%) in the larynx, and 4 (13%) in the nasopharynx. Seventeen patients (53%) had ≥2 prior lines of therapy. Twenty-one patients (66%) experienced a treatment-related adverse event (TRAE), with three experiencing grade 3 TRAEs and one experiencing a grade 4 TRAE (per CTCAE v4.0). No grade 5 TRAEs were reported. Objective responses by Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST v1.1) occurred in 22% of patients, with a median duration of response of 7.4 months (range 2.8–45.8 months). Median progression-free survival was 2.6 months (range 0.5–48.4 months), and median overall survival was 6.0 months (range 0.5–51.6+ months). Responses showed no association with HPV status or PD-L1 expression level. Conclusions: In this heavily pre-treated advanced HNC cohort, atezolizumab had a tolerable safety profile and encouraging activity, with responses observed regardless of HPV status and PD-L1 expression level. These findings warrant further investigation of atezolizumab in HNC. ClinicalTrials.gov number: NCT01375842.